Nascere e morire: quando decido io? Italia ed Europa a confronto - Baldini, Gianni; Soldano, Monica (Studi e saggi, 2011)
This book continues the collaboration between the department of BioLaw of the University of Florence and the non-profit association Madre Provetta, to contribute to a project of study and research that can build towards a common European law on Bioethics. In view of the professional activity in which they are engaged, the authors are among the leading experts in their respective fields on the issues addressed. Biotechnologies have rendered both birth and death more complex, which explains why the approach must be multidisciplinary. In effect, the research ranges from the medical and scientific sphere to the fields of law, sociology and philosophy and through to the institutional dimension. The leitmotif is the responsibility and self-determination of the individual: an anthology addressing issues concerning the beginning and the end of life. Particular focus is placed on the aspect of legal update in the light of recent case law, which is increasingly called upon, on the one hand to lend support to the legislator, and on the other to adapt national legislation to the rules and principles emerging from the supranational and European institutions.